In Finance, Size Matters - Lee, Jong-Kun.; Bossone, Biaggio (Washington, D.C. : International Monetary Fund, 2002)
This study investigates the relationship between production efficiency in financial intermediation and financial system size. The study predicts and tests for the existence of "systemic scale economies" (SSEs), whereby value-maximizing intermediaries operating in large systems are expected to have lower production costs and lower costs of risk absorption and reputation signaling than intermediaries operating in small systems. The study investigates different channels through which the SSEs work their effects through the intermediaries and estimates such effects using a large banking data panel. The study shows strongly supporting evidence in favor of SSEs. It also finds that the institutional environment, the risk environment, and market concentration affect significantly the production efficiency of financial intermediaries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet